Effect of Education Levels on North Sumatra Economy - Hastina Febriaty; Murviana Koto; Sri Endang Rahayu (AIBPM Publisher, 2019)
This study aims to determine the level of high school education (SMU) and Higher Education (PT) on the Economy of North Sumatra and to identify the effect of the level of education on the economy in North Sumatra. This type of research is a descriptive study, while the approach used is a quantitative approach with a sample of GRDP data and the Labor Force over 15 years with high school education levels (SMU) and Higher Education (PT) from 20002017. The type of data used is secondary data obtained from the Central Statistics Agency. The analysis technique used is the multiple linear regression analysis (OLS) method. The results of this study indicate that partially the level of high school education (SMA) has a positive and not significant effect on the Economy of North Sumatra and the level of education of the University (PT) has a positive and significant effect on the Economy of North Sumatra while simultaneously the level of high school education (SMU) and Higher Education (PT) has a positive and significant impact on the Economy of North Sumatra.